Chiral inorganic polar BaTiO3/BaCO3 nanohybrids with spin selection for asymmetric photocatalysis - Sun, Yemeng (2025)
Chirality-dependent photocatalysis is an emerging domain that leverages unique chiral light-matter interactions for enabling asymmetric catalysis driven by spin polarization induced by circularly polarized light selection. Herein, we synthesize chiral inorganic polar BaTiO3/BaCO3 nanohybrids for asymmetric photocatalysis via a hydrothermal method employing chiral glucose as a structural inducer. When excited by opposite circularly polarized light, the same material exhibits significant asymmetric catalysis, while enantiomers present an opposite polarization preference. More importantly, the preferred circularly polarized light undergoes reversal with reversal of the CD signal. Systematic experimental results demonstrate that more photogenerated carriers are generated in chiral semiconductors under suitable circularly polarized light irradiation, including more spin-polarized electrons, which inhibits the recombination of electron-hole pairs and promotes the activation of oxygen molecules into reactive oxygen species, thus inducing this asymmetric photocatalytic feature. This study provides valuable insights for the development of highly efficient polarization-sensitive chiral perovskite nanostructures as promising candidates for next-generation, multifunctional chiral device applications.